PENERAPAN COGNITIVE-BEHAVIORAL THERAPY DALAM MENINGKATKAN LOCUS OF CONTROL PESERTA DIDIK YANG MENGALAMI STRES AKADEMIK - Siti Fatimah; Maya Masyita Suherman; Euis Eti Rohaeti (Universitas Sultan Ageng Tirtayasa, 2019)
Difficulties experienced by students will be perceived as a burden that exceeds the limits of students’ ability and may impact negatively on the students way of thinking as well as their behavior as indicated by their inability to assess himself in overcoming obstacles or pressures. Thus, it is necessary for the student to have an ability to control the events or situations that are happening or will happen which are known as locus of control. This study aims to examine the effectiveness of cognitive-behavioral therapy in improving the locus of control of students who experience academic stress. This study uses a quasi-experimental method with a one group pretest-posttest design pattern. The results of a preliminary study of 162 students found that 3.7% of students experienced high academic stress, 35.2% moderate, and 61.1% low. The research subjects were students who were in the categorized as high academic stress as many as 6 people who were then given a locus of control questionnaire to measure the effectiveness before and after the administration of cognitive-behavioral therapy treatments. The results of data analysis obtained 0.028 <0.05 indicated that there was a difference between the level of locus of control before and after treatment is given so that it can be interpreted that cognitive-behavioral therapy gave significant contribution in increasing the locus of control of students who experience academic stress.Keywords: Cognitive-Behavioral Therapy, Locus of Control, Academic Stress.